دراسة سريريّة مقارنة للسيانوإكريلات وخيوط الحرير في إغلاق الشقوق داخل الفمويّة - أسعد, منذر; خليل, عبد الكريم; حمود, لمى (Latakia University Journal -Medical Sciences Series, 2019)
لقد بُرهن بشكل واسع على فوائد استخدام اللاصق النسيجي (السيانواكريلات) في إغلاق الشقوق الجراحية لكن هذه المادة لم تستخدم في سورية بسبب ارتفاع ثمنها مما جعل الدراسات التي تناولت هذه المادة نادرة جداً. ومن هنا جاء هذا البحث لتقييم فعالية هذه المادة في حدثية الإرقاء للشقوق ما بعد العمل الجراحي مقارنة بالإغلاق الكلاسيكي بوساطة الخيوط. تألفت عينة البحث من 21 مريضاً تم تقسيمهم إلى ثلاث مجموعات رئيسية (تشذيب سنخ ثنائي الجانب وقلوع أرحاء منطمرة علوية وسفلية ثنائية الجانب) وكان نوع الدراسة دراسة سريرية مستقبلية مضبوطة تم فيها إغلاق الشقوق الجراحية بعد اختيارها عشوائياً تارة بالخيوط وتارة باللاصق النسيجي. أظهر تحليل البيانات التي تم جمعها أنّ الوقت اللازم لإغلاق الشقوق الجراحية في حالة استخدام اللاصق النسيجي كان أقل بشكل ملحوظ (P<0.05) وكذلك كان الحال بالنسبة للنزف بعد العمل الجراحي. نستنتج بأنّ كلا الطريقتين فعّالة في إغلاق الشقوق الجراحية داخل الفمويّة وكانت الأفضلية للسيانواكريلات بالنسبة للوقت ولحدثية الإرقاء. We have proved largely the benefits of using tissue adhesive (N-Butyl-2-cyanoacrylate) in the closure of surgical incisions, but this material has not been used in Syria because of the high price, making the studies that have found this material very rare. Hence, this research was to evaluate the effectiveness of this material in causing hemostasis of the incisions after the surgery compared with classic closure using suture. The research sample comprised 21 patients who were divided into three main groups (bilateral alveoloplasty and bilateral third molars extraction) and the type of study is prospective controlled clinical study, where the surgical incisions were closed after being chosen at random sometimes with suture and sometimes with tissue adhesive The analysis of the data collected shows that the time for closing incisions in the case of the use of tissue adhesive was significantly lower (P<0.05) as was the case for bleeding postoperative. We concluded that both methods were effective to close the intraoral wound closure, but with preference to (N-Butyl-2-cyanoacrylate) for the time and hemostasis process .